The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.est.9b07718
|View full text |Cite
|
Sign up to set email alerts
|

Lakes at Risk of Chloride Contamination

Abstract: Lakes in the Midwest and Northeast United States are at risk of anthropogenic chloride contamination, but there is little knowledge of the prevalence and spatial distribution of freshwater salinization. Here, we use a quantile regression forest (QRF) to leverage information from 2773 lakes to predict the chloride concentration of all 49 432 lakes greater than 4 ha in a 17-state area. The QRF incorporated 22 predictor variables, which included lake morphometry characteristics, watershed land use, and distance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 58 publications
(80 reference statements)
0
37
0
Order By: Relevance
“…In US Midwestern and Northeastern states alone, Dugan et al. ( 4 ) estimated that there are 2,000 lakes predicted to have Cl − concentrations >50 mg Cl − /L. In the next 50 y, many of those lakes will exceed the US threshold of 230 mg Cl − /L ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In US Midwestern and Northeastern states alone, Dugan et al. ( 4 ) estimated that there are 2,000 lakes predicted to have Cl − concentrations >50 mg Cl − /L. In the next 50 y, many of those lakes will exceed the US threshold of 230 mg Cl − /L ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in regions that experience cold winters, millions of metric tons of inorganic road deicing salts are applied annually to protect the traveling public by improving road safety. After deicing salts dissolve in rainwater and snowmelt, they wash into adjacent surface and ground waters triggering a substantial increase in salinity ( 3 5 )—in some instances, a salinity level that is 25% the concentration of seawater ( 6 ). The application of fertilizers such as potash (potassium chloride [KCl]) and evapotranspiration during intensive irrigation in agricultural operations concentrate salts on the surface of agricultural soils, which are then transported into nearby fresh waters during precipitation events increasing freshwater salinity ( 7 ).…”
mentioning
confidence: 99%
“…For example, in the Alpine region of Tyrol, Austria, an average of 30,000 tons of salt (sodium chloride) are applied annually to approximately 2240 km of roads (Amt der Tiroler Landesregierung, press release). During periods of snow-removal from the roads (which is partly poured into rivers and stored next to them), and especially during melting and precipitation events, these salts might enter the rivers, as it has been shown for a northern Italian catchment (Nava et al 2020) and North American (Crowther and Hynes 1977;Dugan et al 2020) and Scandinavian streams (Ruth 2003). In all the cases, seasonal salinity cycles were synchronized with road salt applications.…”
Section: Introductionmentioning
confidence: 74%
“…Other studies have also demonstrated high levels of salt concentrations during winter months and widespread salinization in different regions of North America (Dugan et al 2017(Dugan et al , 2020. For example, winter concentrations of Clwere elevated above the United States Environmental Protection Agency (USEPA) acute aquatic life water-quality criteria concentration of 860 mg/L and above the USEPA chronic aquatic life water-quality criteria concentration of 230 mg/L in streams of the Midwestern USA, indicating potential for toxicity effects to aquatic life (Corsi et al 2010).…”
Section: Discovery Of Widespread Freshwater Salinization In Humid Regionsmentioning
confidence: 99%